Molecular characterisation of an avian influenza (H5N8) outbreak in backyard flocks in Al Ahsa, Eastern Saudi Arabia, 2017–2018. Issue 1 (1st December 2019) - Hemida, Maged G; Chu, Daniel; Abdelaziz, Adel; Alnaeem, Abdelmohsen; Chan, Samuel Mo Sheung; Peiris, M
Abstract : Background: Avian influenza viruses are still causing major concern not only to the poultry industry but also to human health across the globe. The live poultry markets and the small‐scale local breeding of various species of birds in backyards are still playing important roles in the sustainability of most virulent influenza viruses, especially H5N8. Methods: The authors investigated an outbreak of highly pathogenic avian influenza H5N8 in backyard flocks in Al Ahsa, Eastern Saudi Arabia that occurred in 2017–2018. Results: A range of poultry including chickens, ostriches, ducks, pigeons and turkeys were clinically affected. Phylogenetic analysis suggested that this was a common source outbreak caused by a virus closely related to H5N8 viruses causing outbreaks elsewhere in Saudi Arabia in early 2018. Conclusions: Small backyard flocks are still contributing to the epidemiology and transmission of H5N8.